Strategic Changes in Defense Diplomacy and Organizational Performance from the Perspective of Innovation and Sustainable Synergy - Muchamad Andi Barata; Willy Arafah (Transpublika Publisher, 2026)
The increasingly complex global security environment demands that nations continuously adapt their defense strategies. In this context, defense diplomacy is no longer understood merely as a ceremonial activity, but as a strategic instrument that plays an important role in perception management, conflict prevention, and strengthening a nation’s strategic position. However, the effectiveness of defense diplomacy is largely determined by the performance of the organizations that carry it out, particularly in facing demands for strategic change, innovation, and sustainability synergy. This study aims to analyze strategic change in defense diplomacy and its implications for organizational performance from the perspective of innovation and sustainability synergy. The study uses a qualitative approach with a literature review method of relevant journal articles, academic books, and international institutional reports. Analysis was conducted through narrative and conceptual synthesis to identify patterns, relationships between variables, and research gaps. The results indicate that the organizational performance of defense diplomacy is significantly influenced by internal organizational factors, namely work engagement, communication effectiveness, and organizational facility, which are integrated through strategic change management. Innovation acts as the main driver of organizational adaptation to threat dynamics and technological developments, while sustainability synergy ensures that strategic changes can deliver long-term impact. This study provides a conceptual contribution in the form of an integrative framework that links strategic change in defense diplomacy with sustainable improvement of organizational performance, and can serve as a reference for the development of adaptive and competitive defense policies.